Sexual Exploitation of Children and Adolescents, Human Trafficking and Mega Sporting Events: A Case Study from Brazil. (July 2016) - Neptune, Ronald E
The purpose of this article is to describe the operation of a four-year prevention and awareness campaign organized by an evangelical social action network that mobilized Brazilian local churches to confront the sexual exploitation of children and adolescents before and during the FIFA 2014 World Cup. The aspects explored in this article are: (a) the birth of the campaign; (b) the manner in which an evangelical network served as a catalyst to mobilize the church to confront sexual violence; and (c) the lessons learned from this experience. It was found that the problem of sexual exploitation of children and adolescents can be addressed through an enlightened and engaged church that accepts the biblical mandate to act with justice and mercy to the "least of the least" in our society: children. The church is a sleeping giant that must be awakened to break the silence of sexual violence and be a strong advocate for vulnerable children.